Sensory Nervous System - Heinbockel, Thomas (IntechOpen, 2018)
The sensory nervous system is of critical importance in our daily lives and contributes to our personal well-being and safety as well as communication with others. However, it is only when disease or injury impair its function that we fully appreciate the relevance of our sensory modalities. During the past decades, research of our senses has seen an ever-growing interest in this exciting field of study. This book provides the reader with an overview of the current state-of-the-art of research of our senses and focuses on the most important evidence-based developments in this area. This book addresses both the physiology and pathophysiology of our sensory nervous system ranging from molecular, cellular, and systems to cognitive and behavioral topics. Individual chapters focus on recent advances in specific areas of sensory systems in different model organisms and humans. All chapters represent recent contributions to the rapidly developing field of sensory science.